A population-based comparison of the survival of patients with colorectal cancer in England, Norway and Sweden between 1996 and 2004. Issue 8 (8th February 2011) - Morris, Eva J A; Sandin, Fredrik; Lambert, Paul C; Bray, Freddie; Klint, Åsa; Linklater, Karen; Robinson, David; Påhlman, Lars; Holmberg, Lars; Møller, Henrik
Abstract : Objective: To examine differences in the relative survival and excess death rates of patients with colorectal cancer in Norway, Sweden and England. Methods: All individuals diagnosed with colorectal cancer (ICD10 (International Classification of Diseases, 10th revision) C18–C20) between 1996 and 2004 in England, Norway and Sweden were included in this population-based study of patients with colorectal cancer. The main outcome measures were 5-year cumulative relative period of survival and excess death rates stratified by age and period of follow-up. Results: The survival of English patients with colorectal cancer was significantly lower than was observed in both Norway and Sweden. Five-year age-standardised colon cancer relative survival was 51.1% (95% CI 50.1% to 52.0%) in England compared with 57.9% (95% CI 55.2% to 60.5%) in Norway and 59.9% (95% CI 57.7% to 62.0%) in Sweden. Five-year rectal cancer survival was 52.3% (95% CI 51.1% to 53.5%) in England compared with 60.7% (95% CI 57.0% to 64.2%) and 59.8% (95% CI 56.9% to 62.6%) in Norway and Sweden, respectively. The lower survival for colon cancer in England was primarily due to a high number of excess deaths among older patients in the first 3 months after diagnosis. In patients with rectal cancer, excess deaths remained elevated until 2 years of follow-up. If the lower excess death rate in Norway applied in the English population, then 890 (13.6%) and 654 (16.8%) of the excess deaths in the colon and rectal cancer populations, respectively, could have been prevented at 5 years follow-up. Most of these avoidable deaths occurred shortly after diagnosis. Conclusions: There was significant variation in survival between the countries, with the English population experiencing a poorer outcome, primarily due to a relatively higher number of excess deaths in older patients in the short term after diagnosis. It seems likely, therefore, that in England a greater proportion of the population present with more rapidly fatal disease (especially in the older age groups) than in Norway or Sweden.